2020
DOI: 10.5296/jas.v8i2.16682
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity on 'BRS 8381' Glycine max (L.) Merril Agronomic Attributes in Different Years of Cultivation in Roraima

Abstract: Soy has high plasticity, which expands its capacity to adapt to different environmental and management conditions, through morphological changes in production components. Thus, the objective was to evaluate the effects of different densities of soybean cultivar BRS 8381 on agronomic characteristics. The experiment was implemented and conducted in a Cerrado area, in the Agua Boa of Embrapa Roraima experimental field. A randomized block design was used in a 2*4 factorial scheme, with four replications. The treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…As well as the results gathered in this paper, other studies have also confirmed that alternative and mineral fertilization induce superiority in the agronomic attributes of several oilseeds and annual crops in successive plantations (Smiderle et al, 2020). This type of fertilization is described as effective in the field because it induces efficiency in physiological processes that promote rapid initial growth of plants (Krenchinsk et al, 2018).…”
Section: Experiments I: Brs Sertaneja Ricesupporting
confidence: 80%
See 2 more Smart Citations
“…As well as the results gathered in this paper, other studies have also confirmed that alternative and mineral fertilization induce superiority in the agronomic attributes of several oilseeds and annual crops in successive plantations (Smiderle et al, 2020). This type of fertilization is described as effective in the field because it induces efficiency in physiological processes that promote rapid initial growth of plants (Krenchinsk et al, 2018).…”
Section: Experiments I: Brs Sertaneja Ricesupporting
confidence: 80%
“…The irrigation was executed by sprinklers, in order to keep the soil moist, when necessary. The treatments related to the control of pests, diseases, and spontaneous plants for soybean crops in the Roraima Cerrado were performed according to the recommendations of Smiderle et al (2020).…”
Section: Experiments Ii: Soybean Production In R 6 Stage (Edamame) In...mentioning
confidence: 99%
See 1 more Smart Citation